If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27a + -45b + -9c = 0 Solving 27a + -45b + -9c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '45b' to each side of the equation. 27a + -45b + 45b + -9c = 0 + 45b Combine like terms: -45b + 45b = 0 27a + 0 + -9c = 0 + 45b 27a + -9c = 0 + 45b Remove the zero: 27a + -9c = 45b Add '9c' to each side of the equation. 27a + -9c + 9c = 45b + 9c Combine like terms: -9c + 9c = 0 27a + 0 = 45b + 9c 27a = 45b + 9c Divide each side by '27'. a = 1.666666667b + 0.3333333333c Simplifying a = 1.666666667b + 0.3333333333c
| 240=x(.03)12 | | P+p^2+30=0 | | AX=D+BX-C | | 10k+5=5 | | x+(.07*x)=350 | | x+(.07*x)=300 | | 9/11x2/9 | | x+(.07*x)=250 | | 11m+30+m^2=0 | | x+(.07*x)=200 | | 6tan^2x+tanx-15=0 | | 9x^3-8=x-x^2 | | M^2+30=11m | | x+(.07*x)=150 | | 420=420x | | y+2*2=58 | | x+(.07*x)=30 | | x+(.07*x)=20 | | x+(.07*x)=15 | | x+(.07*x)=5 | | 4(x-6)+6=6(x-2)-4 | | 11-h=-10-7h | | -10x+3=0 | | 52-25-3=x+7 | | 8c-4=5c+10 | | 7-2(3x-5)=2+3(4x-7) | | 8(x+5)=6(x-2) | | 26x-6-17x+3=19x-4-10x+16 | | x+5-1=26-14 | | x^2+2=23 | | (11-2x)(6-2x)(x)=40 | | .04(x)+.08(x)=10000 |